COVID-19, School Closures and (Cyber)Bullying in Germany - Helen Rahlff; Ulf Rinne; Hendrik Sonnabend (Institute of Labor Economics (IZA), 2023)
We analyze the prevalence of bullying in Germany during COVID-19, both as a real-life phenomenon (in-person bullying, or in our context: school bullying) and via social media and electronic communication tools (cyberbullying). Using Google Trends data from 2013 to 2022 and exploiting the COVID-19 pandemic as a natural experiment when schools switched to distance learning, we document stark changes in the prevalence of (cyber)bullying in Germany: Our results indicate that during school years affected by COVID-19, online searches for school bullying decreased by about 25 percent, while online searches for cyberbullying increased by about 48 percent during the same periods.
Keywords: H75; I12; I21; I28; I31; 330; school bullying; cyberbullying; Google Trends